Marketing tourism in the digital era and determinants of success factors influencing tourist destinations preferences / Mbarek Rahmoun and Yasser Baeshen - Rahmoun, Mbarek; Baeshen, Yasser Baeshen (Accounting Journal Accounting Research Institute (ARI), 2021)
Tourism development has economic benefits, but there also issues related to complex digital marketing and environmental impacts. Nowadays, customers want fast, accurate and friendly responses from the tourism agencies. Hence, the industry must be able to cope with the demands from the clients by using the latest digital technology. Moreover, economic and environmental sustainability are also essential for the long-term tourism resource management. Therefore, this paper explores sustainable tourism in relation to consumer preferences, which ultimately determines economic implications in terms of net value, contributed capital, and employment. Based on the surveys conducted on 75 travel agencies in Europe, it was found that the key factors to destination preferences are (in descending order): customers' income (67.7%), the exchange rate (63.9%), digital marketing factors (53.4%), respect for the environment (38.6%), and sports activities (33.3%).